Experimental Study and Numerical Simulation of Dynamic Stress-Strain of Directional Blasting with Water Jet Assistance - Dengfeng Su; Dandan Zheng; Lingang Zhao (Shock and Vibration)
Effective control of the explosive energy and the propagation direction of blast-induced crack and minimizing damage of remaining rock mass are the main purposes of directional-controlled blasting. In this paper, the experimental test on blast strain fields affected by water jet slot and blasthole wall protection material is conducted. Next, the FEM software ANSYS/LSDYNA is used to simulate the blast‐induced crack propagation and the blast stress wave transmission of different types of blasthole, and the distribution and evolution law of dynamic blast stress are also analyzed. The results indicate that the existence of blasthole wall protection material is not only beneficial to the “guiding effect” of blast‐induced crack propagation of water jet slot but also beneficial to reduce blast-induced damage of remaining rock mass. Besides, the bigger Dm/rb is, the weaker the “guiding effect” and “blasthole wall protection effect” by water jet slot and wall protection material are.